Production and Food Supply in Espírito Santo and the Pluriannual Plan 2012-2015 - Krauser, Raul Ristow (Geografares, 2018)
The present article tries to understand how the situation of food production and supply in Espírito Santo is dealt by the Pluriannual plan (PPA) 2012-2015. The level of the main food cultures production has fallen substantially as well as the specialized production of some exportable goods. It was noticed that this process has an impact on the prices of food evidenced by the food basket price in Vitória. This process can affect the level of food safety for the locals. Finally, considering the PPA 2012-2015, it was detected that these issues aren’t object of concern or strategies in governmental programs. Keywords: Agrarian Question; Food supplies; Food Security.